2021
DOI: 10.33394/j-ps.v9i2.4410
|View full text |Cite
|
Sign up to set email alerts
|

Self-regulated in a Blended Learning: Case Study On Educational Doctoral candidates

Abstract: This study investigates the use of self-regulated in blended learning by students in doctoral education courses to complete advanced statistics lectures. Self-regulated in blended learning is described in four phases according to Zimmerman, namely planning, monitoring, evaluation, and reinforcing. The participants consisted of five students from 5 different disciplines, and were willing to share their learning experiences. Research data obtained by interview method and analyzed qualitatively. Validation uses t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…For instance, "I set standards for my learning tasks. " This variable was a formative construct in the source study, but further, it was demised by other studies and showed reliable findings (Broadbent et al, 2021;Davis and Hadwin, 2021;Won et al, 2021;Yanti et al, 2021). The dependent variable, which measures task performance, is taken from the research of Widyastuti and Hidayat (2018) and is composed of five items.…”
Section: The Instrumentmentioning
confidence: 89%
“…For instance, "I set standards for my learning tasks. " This variable was a formative construct in the source study, but further, it was demised by other studies and showed reliable findings (Broadbent et al, 2021;Davis and Hadwin, 2021;Won et al, 2021;Yanti et al, 2021). The dependent variable, which measures task performance, is taken from the research of Widyastuti and Hidayat (2018) and is composed of five items.…”
Section: The Instrumentmentioning
confidence: 89%